Romeinse sagen en verhalen - Damsté, Onno, 1896-1973 (Antwerpen : Spectrum, 1958)
Aeneas - Romulus en Remus - Rome - Sabijnse maagdenroof - Tarpeia - Horatii en Cariatii - Horatius - Servius Tullius - Tarquinius - Sibyllijnse boeken - Brutus - Lucretia - Consuls - Brutus - Valerius - Horatius Cocles - Mucisu Cloelia - Coriolanus - Fabriërs - Cremera - Cincinnatus - de Tienmannen - VErginia - Spurius - Falerii - Camillus - Allia - Galliërs - Capitolinus - Ptaetextatus - Manlius? Curtius - Titus - Marcus - Publius - Paptius - Caudijnse passen - Pytthus en Cineas - Rome